Modelling and optimization of electrostatic membrane-based actuators - Maj, Cezary (Wydawnictwo Politechniki Łódzkiej, 2011)
The paper presents methods of electrostatic membrane-based actuators modelling. Based on a combination of the classical and reduced model, a simplified approach fully describing the membrane behaviour under hydrostatic and electrostatic load for various conditions, is proposed. The obtained results have been verified experimentally for various shapes of membranes. Furthermore, a new complex tool for simulation and optimization has been developed.

W niniejszym artykule zostały przedstawione metody modelowania aktuatorów sterowanych elektrostatycznie, opartych na membranie. Zaproponowane podejście, które w pełni opisuje zachowanie membrany pod wymuszeniem hydrostatycznym i elektrostatycznym dla wielu założeń, oparte jest na połączeniu modelu klasycznego i zredukowanego. Wyniki zostały potwierdzone eksperymentalnie dla różnych kształtów membran. Dodatkowo zostały stworzone narzędzia do kompletnej symulacji i optymalizacji.
Modelowanie i optymalizacja mikrosystemów sterowanych siłą elektrostatyczną opartych na membranie